1999
DOI: 10.1525/aa.1999.101.1.143
|View full text |Cite
|
Sign up to set email alerts
|

Where Will the Baby Sleep? Attitudes and Practices of New and Experienced Parents Regarding Cosleeping with Their Newborn Infants

Abstract: An evolutionary perspective on human infant sleep physiology suggests that parent-infant cosleeping, practiced under safe conditions, might be beneficial to both mothers and infants. However, cosleeping is not part of mainstream parenting ideology in the United States or the United Kingdom, and little evidence is available to indicate whether, and under what circumstances, parents sleep with their newborn infants. We present data from an anthropological investigation into the practices and attitudes of new and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
88
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 88 publications
(92 citation statements)
references
References 34 publications
2
88
0
Order By: Relevance
“…The authors found that breast feeders were three times more likely to bedshare and that their data did not link bedsharing to risk of infant death. 5,7 In northern England, Ball et al 4 found that they would have missed half of the routine co-sleepers (bedsharers) had the researchers not asked if the baby was moved or relocated to sleep in a different location at some point in the night! They describe why working class parents in North Tees, England changed their sleeping arrangements from crib to bedsharing.…”
Section: Bottle Feeding-bedsharing Mother-infant Dyads and Breast Feementioning
confidence: 99%
See 2 more Smart Citations
“…The authors found that breast feeders were three times more likely to bedshare and that their data did not link bedsharing to risk of infant death. 5,7 In northern England, Ball et al 4 found that they would have missed half of the routine co-sleepers (bedsharers) had the researchers not asked if the baby was moved or relocated to sleep in a different location at some point in the night! They describe why working class parents in North Tees, England changed their sleeping arrangements from crib to bedsharing.…”
Section: Bottle Feeding-bedsharing Mother-infant Dyads and Breast Feementioning
confidence: 99%
“…4,5 One recent survey in the United States found that during the 1990s the numbers of mothers sharing their bed with their infants for part or all of the night doubled and may have reached as many as 50%. 6 That same survey involving over 10 000 families revealed that breast feeding mothers were three times more likely than bottle feeding mothers to bedshare.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The predominant view is that formula feeding promotes infant sleep while breastfed infants are too demanding, feed too frequently, and do not allow their mothers sufficient sleep through the night (Ball, Hooker, & Kelly, 1999;Brown & Harries, 2015). In both the UK and the US, many parents give night-waking as the reason they switched to formula (Douglas & Hill, 2013) and the idea that feeding the infant formula before bed will help the whole family to sleep better is widely accepted (Rosen, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…An anthropological perspective on infant sleep biology, including the evolutionary underpinnings and developmental benefits of mother-infant co-sleeping, have been described in numerous publications by McKenna and colleagues (McKenna, Mosko et al 1990;McKenna, Thoman et al 1993); Mosko et al 1997) and those of several other biological anthropologists ( Ball 2002( Ball , 2003Ball et al 1999Ball et al , 2000Hrdy 2000;Small 1992Small , 1998Trevathan and McKenna 1994). The behavioural and polysomnographic studies reported by McKenna, Mosko, and colleagues throughout the nineties supported the logical conclusion derived from physiological, evolutionary, historical, psychological and crosscultural data, that sleeping in close proximity to its mother ought to be in an infant"s best interests.…”
Section: Introductionmentioning
confidence: 99%